THE RELATIONSHIP BETWEEN FOOD CONSUMPTION, BREAKFAST HABITS AND PHYSICAL ACTIVITY WITH ACADEMIC PERFORMANCE IN ADOLESCENTS - Dida Mas Dhiyaulhaq; Nur Asiah (Lambung Mangkurat University, 2024)
The Harmonized Test Score (HTS) results indicate that Indonesian children's academic performance is very low, scoring 394, well below the normal score of 625. Grade XI students' skills are similar to those of grade VI students. Eating habits, lifestyle, and physical activity significantly impact adolescent development. A total of 98 students from Health Vocational High School Annisa, Citereup, Bogor participated in this study with the purpose of investigating the relationship between fast food consumption, breakfast habits, and physical activity with academic achievement. Results showed 78. 6% had good academic achievement, 53. 1% frequently consumed fast food, 60. 2% had good breakfast habits, and 71. 4% were physically active. A significant connection was found between breakfast habits and academic achievement (p=0. 037), while fast food consumption (p=0. 418) and physical activity (p=0. 785) showed no significant relationship. Schools should educate about the importance of breakfast and the dangers of fast food and provide healthy canteen options to prevent students from buying fast food when they miss breakfast or lunch.